Deskripsi Pelaksanaan Kegiatan Outbound di Sekolah Dasar Alam Ar-royyan Kota Padang - Neza Aprilia; Wisroni Wisroni; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research was motivated by the high self-confidence of students in the Ar-Royyan Elementary School, especially the first (1) class students who had the courage to appear in front of the class, dare to express their opinions, and dare to write in front of the class during the teaching and learning process. Allegedly the high self-confidence of students because of the implementation of outbound activity programs before the teaching and learning process in school. The purpose of the research is to see an overview of the planning, implementation and evaluation of outbound activities. This type of research is quantitative descriptive. The population of the research was the executive committee of outbound activities at the Ar-Royyan Nature Elementary School (educators and education staff) totaling 50 people. The research sample was taken 50% of the total population of 25 people with simple random sampling technique. Data collection techniques using questionnaires and questionnaire data collection tools. Data analysis technique uses quantitative descriptive technique with percentage calculation. The results of the study found that, (1) planning outbound activities looked very good, (2) the implementation of outbound activities looked very good, and (3) evaluation of the implementation of outbound activities looked very good. Suggestions to the Ar-Royyan Nature Elementary School, (1) in order to maintain the outbound activity program is always carried out at the time of admission of new students, and (2) the implementing committee of outbound activities maintain the quality of the implementation of outbound activities that have been carried out properly.Keywords: Outbound, Confidence